215k views
1 vote
Solve the following...

3(x+2)=-5-2(x-3)


User Seryh
by
4.3k points

1 Answer

0 votes


{ \qquad\qquad\huge\underline{{\sf Answer}}}

Let's solve ~


\qquad \sf  \dashrightarrow \: 3(x + 2) = - 5 - 2(x - 3)


\qquad \sf  \dashrightarrow \: 3x + 6 = - 5 - (2x - 6)


\qquad \sf  \dashrightarrow \: 3x + 6 = - 5 - 2x + 6


\qquad \sf  \dashrightarrow \: 3x + 6 = - 2x + 1


\qquad \sf  \dashrightarrow \: 3x + 2x = 1 - 6


\qquad \sf  \dashrightarrow \: 5x = - 5


\qquad \sf  \dashrightarrow \: x = - 5 / 5


\qquad \sf  \dashrightarrow \: x = - 1

User Mark Locker
by
5.0k points